PENGARUH KEPRIBADIAN DAN KETELADANAN GURU KRISTEN TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMK NEGERI TOMPASO BARU, DITINJAU SECARA TEOLOGIS BERDASARKAN I TIMOTIUS 4:12 - Kewas, Jendry (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Education has an important role to produce quality human resources both in terms of intellectual and spiritual. This is in accordance with the Law of the Republic of Indonesia No. 20 of 2003 concerning National Education System Article 3 which states that "National education functions to develop capabilities and shape the character and civilization of a dignified nation in the context of intellectual life of the nation. National education aims to develop the potential of students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Pay attention to the phenomena that occur among students very alarming, the attitude of students who do not have manners, like fighting, drug users, pornography addicts and this condition is the most common delinquency that occurs among students. While other delinquencies include lying, skipping school, drinking, stealing, abortion, gambling. The focus of this research is the influence of Christian teacher personality and role models on the character building of students in Tompasobaru Vocational School theologically reviewed based on I Timothy 4. Researchers use quantitative research methods based on the philosophy of positivism which are generally carried out on samples taken at random, as well as analyzing data using statistics. Population is a generalization area consisting of objects or subjects which become certain quantities and characteristics determined by researchers to be studied and then drawn conclusions. Personality and example are two interrelated things because both personality and example are both present in the teacher and will appear in the teacher's attitude. The teacher's personality must be based on exemplary living. So, the personality and example of Christian teachers in Tompaso Baru State Vocational School simultaneously influence the formation of students' character in Tompaso Baru State Vocational School.